Os caminhos movediços de Bandeira - Melo, José Eduardo Martins de Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This Study Investigates Manuel Bandeira's discourse and it's movable trait, focusing on the dialogue that can be seen between tradition and modernity, fiction and biography. The starting point is the analysis of how the fusion of these aspects is presented in his writing and also how this fusion turns out to be an element of differentiation in Bandeira's style as a poet and translator. Both the marks of existence as well as the signs of death in the author's production are also studied here. These elements represent Bandeira's two main lines of writing and are used by the poet as a way to conduct the whole set of his literary production to the core of a subject that is reinvented in the gap found between tradition and renewal, invention and experience. To achieve the purpose of this work we use studies on poetry developed by the formalists and we also search for the existence of movable boundary lines in which these elements intersect as conductors; the language of death. To this perspective of formalist analysis, we add the ideas about Florência Garramuño's opaque experiences, adjusted to whatever is produced in Bandeira's work regarding the updating of this concept, in which language, subject and artistic procedure stand, both in his poetic creation as in his translation. Looking at the translated literary production, we end the reflexions of the thesis that observes, in the author's expressiveness, a apace of inseparability among the mentioned elements

Esta tese investiga o traço movediço do discurso de Manuel Bandeira a partir do diálogo que interpõe entre tradição e modernidade, ficção e biografia. O ponto de partida é a análise de como se apresenta a fusão destes aspectos em sua linguagem de forma a constituir-se elemento diferencial de seu estilo enquanto poeta e tradutor. Discutimos as marcas da existência e da morte com as quais alimenta essas duas linhas mestras de sua escritura e conduz o conjunto da obra para o núcleo do sujeito reinventado no espaço entre tradição e renovação, invenção e experiência. Para tanto, utilizamos os estudos sobre poética dos Formalistas e escavamos a existência de um espaço movediço em sua linguagem no qual se interseccionam esses elementos enquanto fios condutores; o espaço da morte. A essa perspectiva de análise formalista agregam-se as idéias sobre a experiência opaca de Florencia Garramuño ajustadas ao que se realiza em Bandeira enquanto atualização deste conceito, de onde se interpõem a língua, o sujeito e o procedimento artístico, tanto em sua obra poética quanto na traduzida. Com o olhar sobre a obra traduzida, finalizamos as reflexões da tese que enxerga na expressividade do autor um espaço de indissociabilidade entre esses elementos
Keywords: Bandeira, Manuel 1886-1968 Crítica e interpretação; Literatura brasileira - Séc XIX - História e crítica; Formalismo (Analise literaria); Morte na literatura; Brazilian literature